La contribución de Kant a los estudios internacionales - Murillo Z., Carlos (2005)
﻿﻿﻿﻿﻿I. Kant’s contribution to International Relations is of great meaning, above all, the offered Perpetual Peace. In fact, it is said a Kantian tradition or culture, as a base to one of the fundamental axis of international relations. However, Kant’s vision has not been analyzed in all of its dimensions; furthermore, it is an attempt of approchement to that contribution.